The effect of combined treatment with canagliflozin and teneligliptin on glucose intolerance in Zucker diabetic fatty rats - Takahiro Oguma; Chiaki Kuriyama; Keiko Nakayama; Yasuaki Matsushita; Kumiko Yoshida; Satoko Kiuchi; Yuka Ikenaga; Yoshinobu Nakamaru; Kumiko Hikida; Akira Saito; Kenji Arakawa; Kozo Oka; et al. (Elsevier, 2015)
To assess the impact of concomitant inhibition of sodium-glucose cotransporter (SGLT) 2 and dipeptidyl peptidase IV (DPP4) for the treatment of type 2 diabetes mellitus (T2DM), the effect of combined treatment with canagliflozin, a novel SGLT2 inhibitor, and teneligliptin, a DPP4 inhibitor, on glucose intolerance was investigated in Zucker diabetic fatty (ZDF) rats. Canagliflozin potently inhibited human and rat SGLT2 and moderately inhibited human and rat SGLT1 activities but did not affect DPP4 activity. In contrast, teneligliptin inhibited human and rat DPP4 activities but not SGLT activities. A single oral treatment of canagliflozin and teneligliptin suppressed plasma glucose elevation in an oral glucose tolerance test in 13 week-old ZDF rats. This combination of agents elevated plasma active GLP-1 levels in a synergistic manner, probably mediated by intestinal SGLT1 inhibition, and further improved glucose intolerance. In the combination-treated animals, there was no pharmacokinetic interaction of the drugs and no further inhibition of plasma DPP4 activity compared with that in the teneligliptin-treated animals. These results suggest that the inhibition of SGLT2 and DPP4 improves glucose intolerance and that combined treatment with canagliflozin and teneligliptin is a novel therapeutic option for glycemic control in T2DM.